2007
DOI: 10.1128/aem.02586-06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Reductant on Growth and Iron Mobilization from Ferrihydrite by the Pseudomonas mendocina ymp Strain

Abstract: Growth of the Pseudomonas mendocina ymp strain on insoluble ferrihydrite is enhanced by exogenous reductants with concurrent increase in soluble iron concentrations. This shows that exogenous reductants play a substantial role in the overall microbial iron bioavailability. The exogenous reductants may work together with the siderophores, Fe-scavenging agents, to facilitate ferrihydrite dissolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
(17 reference statements)
3
16
0
Order By: Relevance
“…3B). Such a result is not unexpected, since it has been reported that more complete dissolution of iron oxide deposits in siderophore-based desorption efforts involves contributions from small-molecule reductants (39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 78%
“…3B). Such a result is not unexpected, since it has been reported that more complete dissolution of iron oxide deposits in siderophore-based desorption efforts involves contributions from small-molecule reductants (39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 78%
“…One explanation is that there is some level of interconversion of the iron between ferrous and ferric forms in the agar that is influenced by a complex set of factors including oxidation following exposure to air on the surface and reduction promoted by cysteine in the medium (CDM contains 0.02% cysteine as supplement because the bacteria are defective in sulfate assimilation and require cysteine for growth (26)). Cysteine is known to reduce ferric salts in bacterial media (33). We found that increasing cysteine levels in the CDM agar reduced the extent of growth promotion of the ⌬fupA mutant by ferric iron, presumably because more of the iron was converted to the ferrous form (data not shown).…”
Section: Transport Of Ferrous Iron In Schu S4mentioning
confidence: 70%
“…P. mendocina ymp is known to produce hydroxamatecontaining siderophores that increase the rate of dissolution of the Fe oxide mineral hematite. A recent study demonstrated that reductants significantly enhanced the bioavailability of Fe-(hydr)oxide minerals to P. mendocina (15). The ymp strain was also shown to have endogenous Fe(III)-reducing activity, which Hersman et al suggested could be involved in solubilizing ferric minerals (24).…”
Section: Is 10mentioning
confidence: 99%
“…Likewise, it has been suggested that organic reductants may work synergistically with siderophores. In particular, a recent study showed that exogenously added reductants significantly enhance the bioavailability of Fe to an aerobic siderophore-producing bacterium, Pseudomonas mendocina ymp (15), isolated from the Nevada Test Site and used in the work described here.…”
Section: Is 10mentioning
confidence: 99%